Pan-Cancer Analysis of FURIN as a Potential Prognostic and Immunological Biomarker - Zhou, Bolun; Gao, Shugeng (Frontiers in Molecular Biosciences, 2021)
Background: Furin is a calcium‐dependent protease that processes various precursor proteins through diverse secretory pathways. And the deregulation of FURIN correlated with patients’ prognosis in numerous diseases. Also, the spike protein of SARS-CoV-2 is found to be uniquely cleaved by furin, which may be one cause of its strong epidemic intensity. However, the role of FURIN in human pan-cancer is still largely unknown. Methods: Multiple bioinformatics methods were employed to comprehensively analyze the correlation of FURIN expression with prognosis, mismatch repair (MMR), microsatellite instability (MSI), tumor mutational burden (TMB), DNA methylation, tumor immune infiltration, and common immune checkpoint inhibitor (ICIs) from the public database, and aim to evaluate the potential prognostic value of FURIN across cancers. Results: FURIN was aberrantly expressed and was strongly correlated with MMR, MSI, TMB, and DNA methylation in multiple types of cancer. Moreover, survival analysis across cancers revealed that FURIN expression was correlated with overall survival (OS) in four cancers, disease-specific survival (DSS) in five cancers, progression-free interval (PFI) in seven cancers, and disease-free interval (DFI) in two cancers. Also, FURIN expression was related to immune cell infiltration in six cancers and ImmuneScore/StromalScore in ten cancers respectively. And FURIN expression also showed strong association between expression levels and immune checkpoint markers in three cancers. Conclusion: FURIN can serve as a significant prognostic biomarker and correlate with tumor immunity in human pan-cancer.